Natural diversity uncovers P5CS1 regulation and its role in drought stress tolerance and yield sustainability in barley. (3rd October 2022) - Shrestha, Asis; Fendel, Alexander; Nguyen, Thuy H.; Adebabay, Anteneh; Kullik, Annika Stina; Benndorf, Jan; Leon, Jens; Naz, Ali A.
Abstract: Proline accumulation is one of the major responses of plants to many abiotic stresses. However, the significance of proline accumulation for drought stress tolerance remains enigmatic in crop plants. First, we examined the natural variation of the pyrolline‐5‐carboxylate synthase ( P5CS1 ) among 49 barley genotypes. Allele mining identified a previously unknown allelic series that showed polymorphisms at 42 cis‐ elements across the P5CS1 promoter. Selected haplotypes had quantitative variation in P5CS1 gene expression and proline accumulation, putatively influenced by both abscisic acid‐dependent and independent pathways under drought stress. Next, we introgressed the P5CS1 allele from a high proline accumulating wild barley accession ISR42‐8 into cultivar Scarlett developing a near‐isogenic line (NIL‐143). NIL‐143 accumulated higher proline concentrations than Scarlett under drought stress at seedling and reproductive stages. Under drought stress, NIL‐143 showed less pigment damage, sustained photosynthetic health, and higher drought stress recovery compared to Scarlett. Further, the drought‐induced damage to yield‐related traits, mainly thousand‐grain weight, was lower in NIL‐143 compared with Scarlett in field conditions. Our data uncovered new variants of the P5CS1 promoter and the significance of the increased proline accumulation regulated by the P5CS1 allele of ISR42‐8 in drought stress tolerance and yield stability in barley.